Knowledge, Perception and Attitude on Otitis Media Among Parents With Children 5 Years and Below - Opoku Agyemang, Cecilia; Cobbinah, Joanitha; Addae Nyame, Henrietta; Owusu Opoku, Abigail; Agyemang Opoku, Oscar (Pusat Publikasi Nusantara, 2023)
Otitis media is an inflammation of the middle ear mucosa presenting with symptoms of otalgia, fever, ear tugging, frequent crying at night and ear discharge through a tympanic membrane perforation. Globally, otitis media is a common health problem among children and causes an unpleasant feeling and complications to children. The purpose of this study is to determine knowledge, perception and attitude on otitis media among parents of children five years and below who seek health care at Abuakwa Polyclinic. This study used a quantitative cross-sectional design and 114 parents of children 5 years and below were recruited using non-probability method of convenient sampling. The findings suggest that the surveyed parents had a reasonable level of knowledge regarding otitis media. They generally understood that it is an infection and inflammation of the middle ear, recognized common risk factors, and can identify the typical clinical manifestations. The findings reveal varied perceptions and knowledge among parents regarding otitis media. While there is generally a good understanding of certain aspects such as causative organisms, clinical manifestations, and complications, there are also areas where misconceptions or uncertainty exist, such as the need for antibiotics and the long-term prognosis of the condition. The findings highlight the diverse attitudes of parents towards otitis media. A significant number of parents demonstrate a proactive approach by seeking prompt treatment and opting for hospital care, there are also variations in treatment preferences, with a minority favoring traditional or alternative methods. Factors such as accessibility, waiting times, previous experience, financial constraints, treatment effectiveness were socio-economic factors influencing parents attitude and their choice of where to seek care. The study recommends that ENT professionals in collaboration with the district public health team are to initiate and implement health education programs on otitis media to create more awareness among parents with children 5 years and below